Tingkat Kepedulian Mahasiswa terhadap Lingkungan Kampus yang Bersih dan Hijau - Assyifa Luthfiah H; Nadira Hasan Harahap; Riska Fadhilah D; Sri Mulyeni (Pusat Riset dan Inovasi Nasional, 2026)
Increasingly complex environmental problems, including pollution, ecosystem degradation, and climate change, demand greater awareness and active participation from all sectors of society, particularly students as agents of change. A clean and green campus environment is essential for supporting comfort, health, and the sustainability of academic activities. As centers of education and innovation, universities hold a strategic responsibility to cultivate environmental awareness through the implementation of the green campus concept. This study aims to examine the level of student awareness regarding campus cleanliness and greening based on findings from previous research. The method employed is a literature review, analyzing various relevant sources such as scientific journal articles, academic books, and policy documents related to sustainable campus management. The analysis was conducted using a descriptive qualitative approach to identify recurring patterns, prevailing trends, and key factors influencing students’ environmental awareness and behavior. The results indicate that student awareness levels generally fall within the fair to good category. Students with higher environmental awareness tend to participate more actively in maintaining cleanliness and supporting campus greening initiatives. However, the development of environmentally responsible behavior is strongly influenced by adequate facilities, supportive institutional policies, and a sustainability-oriented campus culture. Therefore, strengthening the role of higher education institutions through comprehensive environmental policies and structured sustainability programs is crucial to fostering clean, green, and sustainable campuses.